Efforts to Improve Local Wisdom-Based Science Learning Outcomes With The TGT Model For Grade IV Students at SDN 128 Palembang - Septia, Delfi; Siahaan, Sardianto Markos; Masfufah, Annasriyah (Universitas Nusantara PGRI Kediri, 2025)
This study aims to improve the learning outcomes of 15 fourth grade students in science material based on local wisdom with the Teams Games Tournament (TGT) model with the type of classroom action research (PTK) to analyze learning outcomes from the pre-cycle and pre-cycle. then apply treatment with the Teams Games Tournament (TGT) model in cycle I and cycle II. The results of the study showed that after the pre-cycle the average student learning score was 35%, in cycle II the average score was 79.3% and in cycle II the average score was 87%. In conclusion, there is a significant increase in the implementation of the independent curriculum of the Teams Games Tournament (TGT) model on social studies learning outcomes based on local wisdom. The participatory learning model has a positive impact on the development of effective learning.